Consórcio capim-marandu e amendoim forrageiro: produção, bromatologia e ciclagem de nutrientes - Luiza Elvira Vieira Oliveira Valente (2017)
The legumes can contribute to the nitrogen supply to the consortium system, via biological fixation, resulting from the symbiosis between the legume and the bacteria of the genus Rhizobium, thereby favoring the growth and development of the grass, increasing its productivity, quality and cycling of the nutrients in the system. In this context, the objective was to evaluate forage production, a bromatological composition and a nutrient cycling of marandu grass, whether or not intercropped with forage peanuts. The experimental design used for the adjustment of the time, considering the seasons of the year (autumn, winter, spring and summer). A nutrient cycling was determined at six soil depths (0-5, 5-10, 10-15, 15-20, 20-40 and 40-60 cm). The experiment was carried out at the Experimental Station of Zootecnia of the Extreme South of Bahia, of the Comissão Executiva do Plano da Lavoura Cacaueira - CEPLAC, located in Itabela (16039'S and 39030'O), during the period from March 2013 to April 2014. For A determination of the forage production and the bromatological constituents was performed every 28 days a double sampling of forage present in metallic square with an area of 1 m². The collected material was separated into dead material, green material, leaf, stem and whole peanut plant. As samples of roots were collected with an iron cube (20x20x20 cm). As litter samples were collected in a 20x20 cm iron frame. Afterwards, all samples were weighed, dried, coins and sent to the laboratory. The evaluated properties were: green forage production (PMV), dry matter production (PMS), dry matter (DM), crude protein (CP), neutral detergent fiber (NDF) and carbon isotope-13. A nutrient cycling was also evaluated for macro and micro nutrient content. An ANOVA and a 5% probability result were performed. There were no interaction effects between the management systems and the seasons (p>0.05), but there was an effect (p<0.05) between forage production systems. As averages for PMV were 17.75 and 25.21% for the consortium and monoculture respectively. For PMS as averages were 33.88 and 35.89% for the consortium and monoculture respectively. In the total forage mass (MFT) during the pre-grazing of cattle in the levels of PB, NDF, FDA were 10.10 and 9.48%, 77.38 and 79.58%, 51.07 and 50.50% for the consortium and monoculture, respectively. For Carbon-13 as averages were -17.09 and 14.84 () for the consortium and monoculture respectively. The carbon stock presented an effect between systems (p<0.05) with averages, for a layer of 0-5cm of depth, of 3.36 and 3.77 kg dm-3 of C for the consortium and monoculture respectively. For pre-grazing forage fractions, there was an effect (p>0.05) between the two systems regarding total nutrient content. The MV fraction in the consortium presented a total of 306.97 mg kg and not a total monoculture of 302.82 mg kg. There was an effect (p> 0.05) between the soil chemical attributes for the two systems. In the consortium the contents of P, S and K were 3.80, 6.80 and 81.07 mg dm-3. In the monoculture the contents of P, S and K were 5.35, 9.19 and 88.25 mg dm-3. The consortium between grasses and legumes in the pasture can be used for cattle production under grazing with good results in the productive, bromatological and nutrient cycling.